Electrochemical Detection of a Novel Pt(IV) Prodrug with the Metronidazole Axial Ligand in the Hypoxic Area - Spector, Daniil V.; Erofeev, Alexander S.; Gorelkin, Petr V.; Vaneev, Alexander N.; Akasov, Roman A.; Ul’yanovskiy, Nikolay V.; Nikitina, Vita N.; Semkina, Alevtina S.; Vlasova, Kseniya Yu; Soldatov, Mikhail A.; Trigub, Alexander L.; Skvortsov, Dmitry A.; et al. (Inorganic chemistry, 2022)
We report herein a Pt(IV) prodrug with metronidazole in axial positions Pt-Mnz. The nitroaromatic axial ligand was conjugated with a cisplatin scaffold to irreversibly reduce under hypoxic conditions, thereby retaining the Pt(IV) prodrug in the area of hypoxia. X-ray near-edge adsorption spectroscopy (XANES) on dried drug-preincubated tumor cell samples revealed a gradual release of cisplatin from the Pt-Mnz prodrug instead of rapid intracellular degradation. The ability of the prodrug to penetrate into three-dimensional (3D) spheroid cellular cultures was evaluated by a novel electrochemical assay via a platinum-coated carbon nanoelectrode, capable of single-cell measurements. Using a unique technique of electrochemical measurements in single tumor spheroids, we were able to both detect the real-time response of the axial ligand to hypoxia and establish the depth of penetration of the drug into the tumor model.